2019
DOI: 10.1177/1071181319631196
|View full text |Cite
|
Sign up to set email alerts
|

How do Individual Differences in Attention Control and Working Memory Capacity Relate to Monitoring Automation?

Abstract: With the proliferation of automated tasks, software, and systems, humans are moving from an active participant in the function of a task to a passive monitor of an automated system that is completing that task. Unfortunately, humans are not well-suited for monitoring roles and there is a need to better understand the factors involved when humans successfully identify when an automated system fails. The goal for this research was to determine whether individual differences in attention control (as measured by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…These findings support those of Foroughi et al (2019) and expand the literature by introducing high-level automation. Our results also allow for a more granular understanding of the relationship between AC and the use of unreliable automation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These findings support those of Foroughi et al (2019) and expand the literature by introducing high-level automation. Our results also allow for a more granular understanding of the relationship between AC and the use of unreliable automation.…”
Section: Discussionsupporting
confidence: 88%
“…In precisely the situations where automation is typically implemented (high workload, multitasking situations), the ability to control attention seems crucially important. Indeed, in the first empirical demonstration of a link between AC and automation performance, Foroughi et al (2019) observed a positive relationship between AC and failure detection using a supervisory control task. In their study, participants completed a task where they had to monitor a trisected screen which had various shapes flowing through each section.…”
Section: Individual Differences In Working Memory and Attentional Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, positive correlational relationships have been found between WM scores as measured by the shortened Ospan (Foster et al, 2015) and the ability to notice automation failures (Foroughi et al, 2019). High spans detected more automation failures.…”
Section: Review Working Memory and Automationmentioning
confidence: 90%
“…SA was measured with a change detection task. High spans are better at noticing (Foroughi et al, 2019) and managing automation failure (Jipp, 2016), which can be characterized as departures from normal operation. The other 3 automation levels did not provide this flexibility.…”
Section: Review Working Memory and Automationmentioning
confidence: 99%